Factors Influencing Histologic Confirmation of High-Grade Squamous Intraepithelial Lesion Cytology - Castle, Philip E. (2008)
OBJECTIVE: To examine the predictors of histologic confirmation of high-grade squamous intraepithelial lesion (HSIL) cytology occurring in follow-up of young women originally referred into a trial because of less severe cytology. METHODS: We used enrollment HSIL cytology (n = 411) as read by clinical center pathologists for women participating in the Atypical Squamous Cells of Undetermined Significance (ASCUS) and Low-Grade Squamous Intraepithelial Lesion (LSIL) Triage Study (ALTS). The primary outcome was histologic cervical intraepithelial neoplasia grade 3 (CIN3) and early cancer (n = 195; 191 CIN3 and 4 cancers) as diagnosed by the quality control (QC) Pathology group over the 2-year duration of ALTS. RESULTS: The 2-year absolute risk of CIN3 or worse following a HSIL cytology was 47.4% (95%CI = 42.5%–52.4%). The 2-year absolute risk of CIN3 or worse was lowest (14.3%) for women who were HPV16 negative, had colposcopic impression of less than low-grade, and whose HSIL cytology as called by the clinical center was not also called HSIL or equivocal HSIL cytology by QC Pathology. The 2-year absolute risk of CIN3 or worse was highest (82.4%) for women who were HPV16 positive, had colposcopic impression of low-grade or worse, and whose HSIL cytology was also called HSIL or equivocal HSIL cytology by QC Pathology. CONCLUSIONS: Histologic confirmation of precancer among young women with HSIL cytology was more likely when other risk factors (e.g., HPV16) for cervical precancer were present.